LITERACIES AND DIGITAL GAMING: NEGOTIATING MEANINGS IN ENGLISH LANGUAGE TEACHER EDUCATION - Vanderlei J. Zacchi (Universidade Federal de Sergipe, 2019)
Digital epistemologies in the area of literacies and language teaching are becoming increasingly important, due to the radical transformations that our society is undergoing as a result of the advent of the new technologies of communication and of processes linked to globalization. It is a quite relevant and pressing issue, since children and the youth are coming to school in possession of a great deal of knowledge about and competence with digital tools and discourses. On the other hand, there are still a great number of students that lack digital literacy and face difficulties in reading from the screen. Taking into account the fact that the research on digital games and language teaching in Brazil is very incipient, the aim of this project is to examine ways that literacies and digital games can be combined to improve English language teaching in Sergipe and Brazil. Connecting all these topics may bring innovative results with potential to be applied to English language teaching and teacher education and solidify the research in this area.